Pengaruh Disiplin Kerja terhadap Kinerja Karyawan PT Pendekar Bodoh (D'cost) - Dona Fitria; Burhanudin Burhanudin; Nurlaela Nurlaela (Neolectura, 2021)
This study aims to determine the effect of work discipline on the performance of employees of PT. Pendekar Bodoh (Dcost). The method used is a quantitative method. The population is employees of PT. The Stupid Swordsman (Dcost) totaling 125 people and the sample taken as many as 95 people using the